A new model of patient-centred care for general practitioners: results of an integrative review. (31st October 2019) - Brickley, Bryce; Sladdin, Ishtar; Williams, Lauren T; Morgan, Mark; Ross, Alyson; Trigger, Kellie; Ball, Lauren
Abstract: Background: GPs providing patient-centred care (PCC) is embedded in international health care policies due to its positive impact on patients and potential to lower health care costs. However, what is currently known about GP-delivered PCC is unknown. Objective: To synthesize literature investigating GP-delivered PCC and address 'what is currently known about GP-delivered PCC?' Method: A systematic literature search was conducted between June and July 2018. Eligible articles were empirical, full-text studies published in English between January 2003 and July 2018, related to at least three of the four dimensions of PCC described by Hudon et al . (2011), and related to preventative, acute, and/or chronic care by GPs. Following screening, full-text articles were independently assessed for inclusion by two investigators. Data were extracted and quality assessed by two researchers. Findings on PCC were analysed thematically (meta-synthesis). Results: Thirty medium- to high-quality studies met the inclusions criteria. Included studies utilized varied designs, with the most frequent being quantitative, cross-sectional. A theoretical model of PCC was synthesized from included studies and contained four major components: (i) understanding the whole person, (ii) finding common ground, (iii) experiencing time and (iv) aiming for positive outcomes. Harms of PCC were rarely reported. Conclusions: Four overarching theoretical components of PCC relate to elements of the consultation and experience of time. These components can be used to inform the development of toolkits to support GPs and general practice organizations in pursuit of PCC as well as tools to measure patient-centredness.